(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
While defining the technology stack for creating native AR apps for iOS, developers are faced with the need to choose between two popular Apple graphics frameworks: SceneKit and RealityKit. Most available studies are dedicated to the analysis of their internal architecture and most beneficial technical capabilities. Whereas this study focuses on the fundamental comparison of the frameworks using the multi-criteria decision analysis method. For this, the significant qualitative and quantitative comparison criteria are highlighted, as well as a series of experiments are conducted to compare frameworks in terms of scene rendering performance (FPS) and mobile device resource usage (CPU, GPU). Such a formal approach makes it possible to evaluate the effectiveness of frameworks and their suitability for different project types and development teams. This allows developers to make informed decisions during the design stage according to their needs. Confirming the potential of the proposed approach in practice, an example of its application to select the most appropriate framework for two different AR projects is presented. The specificity of applying this approach in the context of the current task was highlighted.